Problem Based Learning Model Development by Blended Learning and Google Classroom Media in Public SHS 1 Sale Rembang - Junipah, Junipah; Kardoyo, Kardoyo; Yulianto, Arief (Universitas Negeri Semarang, 2019)
Learning achievement of economy lesson at Public SHS I Sale has not met minimum passing grade. Therefore, there is a need to develop practice and effective learning model to improve it. This research aims to describe and analyze economy lesson learning in the school. To find out problem based learning model design through blended learning aided by Google Classroom and to analyze practicability and effectiveness of the learning model aided by blended learning and Google Classroom media in learning. This Research and Development was done in three stages: preliminary, product development, and product evaluation. Techniques of collecting data used questionnaire, observation, and test. The preliminary stage presented factual learning model. The development stage was initiated by designing model, expert and practitioners’ validation, and trial run. Evaluating step was done by two random selection design and pre-test and post-test to find out practicability and effectiveness of the model was done by Wilcoxon. The findings showed poor factual learning model, problem based learning model development with blended learning aided by Google Classroom, and product trial run and product reliability test. The observation and questionnaire of the students showed that the model development was implemented. The finding of reliability test showed post-test of experimental group was higher. It showed the product was practice and effective to be implemented in the school.